Dopaminergic Neurons Respond to Iron-Induced Oxidative Stress by Modulating Lipid Acylation and Deacylation Cycles - Sánchez Campos, Sofía (2015)
Metal-imbalance has been reported as a contributor factor for the degeneration of dopami-nergic neurons in Parkinson Disease (PD). Specifically, iron (Fe)-overload and copper (Cu)mis-compartmentalization have been reported to be involved in the injury of dopaminergicneurons in this pathology. The aimof this work was to characterize themechanisms ofmembrane repair by studying lipid acylation and deacylation reactions and their role in oxi-dative injury in N27 dopaminergic neurons exposed to Fe-overload and Cu-supplementa-tion. N27 dopaminergic neurons incubated with Fe (1mM) for 24 hs displayed increasedlevels of reactive oxygen species (ROS), lipid peroxidation and elevated plasma membranepermeability. Cu-supplemented neurons (10, 50μM) showed no evidence of oxidativestress markers. A different lipid acylation profile was observed in N27 neurons pre-labeledwith [3H] arachidonic acid (AA) or [3H] oleic acid (OA). In Fe-exposed neurons, AA uptakewas increased in triacylglycerols (TAG) whereas its incorporation into the phospholipid (PL)fraction was diminished. TAG content was 40% higher in Fe-exposed neurons than in con-trols. This increase was accompanied by the appearance of Nile red positive lipid bodies.Contrariwise, OA incorporation increased in the PL fractions and showed no changes inTAG. Lipid acylation profile in Cu-supplemented neurons showed AA accumulation intophosphatidylserine and no changes in TAG. The inhibition of deacylation/acylation reac-tions prompted an increase in oxidative stress markers andmitochondrial dysfunction in Fe-overloaded neurons. These findings provide evidence about the participation of lipid acyla-tionmechanisms against Fe-induced oxidative injury and postulate that dopaminergic neu-rons cleverly preserve AA in TAG in response to oxidative stress.